2022
DOI: 10.1111/adj.12923
|View full text |Cite
|
Sign up to set email alerts
|

Impact of molar incisor hypomineralization on oral hygiene and gingival health in 8–15‐years‐old children

Abstract: Background: This study aimed to evaluate the impact of molar incisor hypomineralization (MIH) on oral hygiene and gingival health, and to investigate the relationship between these factors and the severity of MIH. Methods: A total of 72 children (48 with MIH and 24 healthy controls) were included in the study. MIH severity was categorized into three groups:mild (n = 16), moderate (n = 16) and severe (n = 16).The modified-Quigley Hein plaque index (m-QHPI) was used to determine oral hygiene, and the gingival in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…It is probable that the correlation between MIH and increased experience of caries in children is due to the fact that hypersensitivity acts as a barrier to the proper and regular performance of oral hygiene measures at home [ 96 ]. A recent clinical study on oral hygiene and gingival health among children with MIH showed that plaque index, gingival index, and bleeding on probing were significantly higher in the MIH group than in the control group, and they also correlated with MIH severity [ 97 ]. In fact, Raposo et al demonstrated in a large sample of children with MIH that dental hypersensitivity affects more than half of the molars with either moderate or severe forms of MIH.…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that the correlation between MIH and increased experience of caries in children is due to the fact that hypersensitivity acts as a barrier to the proper and regular performance of oral hygiene measures at home [ 96 ]. A recent clinical study on oral hygiene and gingival health among children with MIH showed that plaque index, gingival index, and bleeding on probing were significantly higher in the MIH group than in the control group, and they also correlated with MIH severity [ 97 ]. In fact, Raposo et al demonstrated in a large sample of children with MIH that dental hypersensitivity affects more than half of the molars with either moderate or severe forms of MIH.…”
Section: Discussionmentioning
confidence: 99%
“…Teeth affected by MIH exhibit heightened susceptibility to the rapid development of caries due to increased enamel porosity, structural loss, and exposure of dentinal tubules, thereby facilitating pulpal inflammation (Crombie et al, 2009;Mangum et al, 2010). The complications in teeth affected by MIH are exacerbated by children's tendencies to avoid brushing, leading to increased dental plaque stagnation (Türkmen & Özükoç, 2022).…”
Section: Introductionmentioning
confidence: 99%